High dose ESAs are associated with high iPTH levels in hemodialysis patients with end-stage kidney disease: a retrospective analysis - Lan eChen; Yi-sheng eLing; Chun-hua eLin; Jin-Xuan eHe; Tian-Jun eGuan (Frontiers Media S.A., 2015)
Objective: Anemia and secondary hyperparathyroidism are the two most common complications associated with chronic kidney disease (CKD). Erythropoiesis-stimulating agents (ESAs) are widely used in the management of anemia in hemodialysis patients. A reverse correlation has been established between hyperparathyroidism and hemoglobin levels. The aim of this retrospective study is to evaluate the relationship of high dose ESAs and hyperparathyroidism in hemodialysis patients with anemia. Methods: A total of 240 uremic patients maintained on regular hemodialysis were enrolled into this study. Among them, 142 patients were treated with Epiao® (epoetin-alfa) and 98 patients were treated with Recormon® (epoetin-beta). The target hemoglobin concentration was 110-130 g/L. Laboratory measurements including hemoglobin, calcium, phosphorus, albumin, intact-parathyroid hormone (iPTH), serum ferritin and transferrin saturation were collected. Results: Hemoglobin concentration increased as iPTH level decreased by stratification. However, no significant association between anemia and calcium or phosphorus level was found. Patients with iPTH levels within 150-300 pg/mL had the highest levels of hemoglobin, serum ferritin and transferrin saturation. Patients treated with Recormon and Epiao had similar hemoglobin concentrations. However, the dose of Recormon for anemia treatment was significantly less than that the dose of Epiao (P<0.05). The level of iPTH in the Recormon group was significantly lower than in the Epiao group. In patients with hemoglobin levels between 110-130 g/L (P<0.05), iPTH level was found to be significantly lower in patients treated with lower doses of ESAs than in patients treated with higher doses of ESAs, no matter which ESA was used (Recormon or Epiao, P<0.05). Conclusions: The dose of ESAs might be positively associated with iPTH level, suggesting that a reasonable hemoglobin target can be achieved by using the lowest possible ESA dose.